If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11a + -1b + 3a + -1(-7b) = 0 Remove parenthesis around (-7b) 11a + -1b + 3a + -1 * -7b = 0 Multiply -1 * -7 11a + -1b + 3a + 7b = 0 Reorder the terms: 11a + 3a + -1b + 7b = 0 Combine like terms: 11a + 3a = 14a 14a + -1b + 7b = 0 Combine like terms: -1b + 7b = 6b 14a + 6b = 0 Solving 14a + 6b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. 14a + 6b + -6b = 0 + -6b Combine like terms: 6b + -6b = 0 14a + 0 = 0 + -6b 14a = 0 + -6b Remove the zero: 14a = -6b Divide each side by '14'. a = -0.4285714286b Simplifying a = -0.4285714286b
| w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 | | -9h+15=27-2h | | 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 | | 10x+8(x-3)-8= | | -6(x-1)-7=-7x+7 | | 10.8a+9.8a-7.9=-7.6 | | (x+6)((2x-1)(x+6))=0 | | (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x | | R^2-9/2r=29 | | 0=-16t^2+10t+56 | | -25+3x=0 | | 20n-19n+21=-21 | | x=4/3×3.14×7×7×7 |